The Effect of Product Completeness, Store Attributes, and Store Atmosphere on Repurchase Intention Mediated by Customer Satisfaction Alfamart in West Bandung Regency - Nuraeni, Leni Afni; Ernawadi, Yadi (Universitas Batanghari, 2024)
This study aims to examine the effect of Product Completeness, Store Attributes, and Store Atmosphere on Repurchase Intention Mediated by Customer Satisfaction at Alfamart in West Bandung Regency. 117 consumers who experienced shopping at Alfamart in West Bandung Regency were involved as respondents. The method used to collect data is cross-sectional. The instruments that were used have undergone extensive reliability and validity testing. The strategy for data analysis is structural equation modeling (SEM) with SmartPLS version 3.0. Six of the 10 hypotheses that were proposed have been supported by actual data. The result of this study indicates that product completeness, and store attributes have a direct effect on repurchase intention. Meanwhile, store atmosphere has no effect either directly or indirectly on repurchase intention. It is believed that the study's findings would be beneficial for managers and future researchers in the industry being evaluated or similar retail sectors when it comes to developing relevant methods to improve the caliber of these attributes.